1993
DOI: 10.1177/41.4.8450198
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix in regenerating rat sciatic nerve: a comparative study on the localization of laminin, hyaluronic acid, and chondroitin sulfate proteoglycans, including versican.

Abstract: Using a glial hyaluronate-binding protein as a probe, monoclonal antibodies against versican and ABC digested chondroitin sulfate proteoglycans, and polyclonal antibodies against laminin, we localized these extracellular matrix (ECM) components in the endoneurium of the adult rat sciatic nerve. During Widleian degeneration caused by nerve crushing, the staining pattern of these ECM elements changed dramatically. In the first stages and up to 5 days after injury, the tubular endoneurial structures remained the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 2 publications
3
58
1
7
Order By: Relevance
“…In peripheral nerves, HA has positive effects on peripheral nerve regeneration modulating glial cell adhesion and migration and neuronal sprouting [15][16][17]. Yet, topical application of HA is able to reduce the scar formation and create a more favorable environment for nerve regeneration [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In peripheral nerves, HA has positive effects on peripheral nerve regeneration modulating glial cell adhesion and migration and neuronal sprouting [15][16][17]. Yet, topical application of HA is able to reduce the scar formation and create a more favorable environment for nerve regeneration [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…HA action is related to its molecular weight; a long polymer (>500 kDA) is generally known as high molecular weight HA (HMW HA) and is found predominantly in the brain where it has a structural role and takes part in various biological process like silences inflammation, angiogenesis and neural differentiation [14]. In the peripheral nerves, HA is one of the prominent components of the Bunger band formed during Wallerian degeneration, and the ablation of HA receptors can reduce cell adhesion and migration [15]. Several studies showed that HA has a positive effects on peripheral nerve regeneration [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several MAbs recognizing epitopes on chondroitin sulfate chains have been developed and used to visualize the changes in chondroitin sulfate during development, wound healing, and regeneration (Tona et al, 1993;Brittis et al, 1992;Perris et al, 1991;Mark et al, 1990). In this study, three different kinds of MAbs were successfully used to detect PGs that contained chondroitin sulfate chains susceptible to chondroitinase ABC digestion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that the disappearance and reappearance of ECM components play important roles during these processes (Kato et al, 1992;Wewer et al, 1992;Martinez-Hernandez et al, 1991;Rescan et al, 1989;Carlsson et al, 1981;Edward et al, 1980). Changes of chondroitin sulfate proteoglycans (PGs) as a component of the extracellular matrix have been observed in other systems for tissue regeneration and development: skeletal muscle regeneration (Carrino et al, 1988); optic nerve regeneration (Battisti et al, 1992); retinal neuronal patterning (Brittis et al, 1992); neural crest development (Perris et al, 1991); tooth germ development (Mark et al, 1990); sciatic nerve regeneration (Tona et al, 1993;Hoffman et al, 1990); and kidney development (McCarthy et al, 1993). However, changes in chondroitin sulfate PGs during liver development and regeneration have remained to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…The extracellular matrix (ECM) is involved in various aspects of brain development (Venstrom and Reichardt, 1993), including nerve regeneration (Masuda-Nakagawa and Nicholls, 1991;Bignami et al, 1991;Tona et al, 1993), migration of neuronal cells, axonal outgrowth (Kafitz and Greer, 1998;Pires-Neto et al, 1999), and cell-to-cell signaling (Arber et al, 1995). About 20% of the weight of the living brain consists of extracellular water associated with the brain ECM that fills the empty spaces between cells (Rutka et al, 1988).…”
Section: Introductionmentioning
confidence: 99%